Experimental and theoretical study of nanotwinned copper fabricated by pulse-reverse electrodeposition for interconnect and through-silicon via (TSV) technologies - Lin, Nay (2014)
Through-silicon via (TSV) copper interconnects of varying sizes and aspect ratios are fabricated using pulse and pulse-reversed electrodeposition techniques in deep reactive ion etched silicon vias. Mechanical properties of fabricated TSV are characterized by nanoindentation. The measurements show the strong influence of electrode geometry on the properties and microstructure of copper. The impurity incorporation at current densities below and above the limiting current density is measured by the secondary ion mass spectroscopy. Strong relationship between mechanical properties and impurity incorporation in TSV is observed. The impurity influence on microstructure of copper TSV with various diameters is also studied and reported. Electron backscatter diffraction (EBSD) experiments on TSV show no preferred orientation. In order to understand the effects of texture on formation of nanotwinned copper, experiments were conducted to evaluate the texture of electroplated copper films of varying thickness using pulse-reverse electrodeposition. It is observed that pulse reverse electroplating produced a deposit with a high volume fraction of (111) textured copper. The initial nucleation studies of copper on (111) textured sputtered gold seed layer show that initial copper grains have strong (111) orientation. Micro-raman measurements of stress evolution in the thin copper films show the stress evolution over time. The role of stress on (111) textured copper crystals is evaluated by first-principle calculations within the framework Generalized Stacking Fault Energy (GSFE) and twinnability. Theoretical calculations show that the biaxial stress has strong effects on the stacking fault energies, unstable and stable stacking and twinning fault energies. It leads to the variation of twinnability in copper with level of biaxial stress. Compressive biaxial stress increases twinnability while tensile stress decreases twinnability. The electromigration reliabilities of nanotwinned copper and aluminum doped copper are also calculated. It is concluded that pure copper has better performance than Al-doped alloys.